Evaluation of concentrations of trace metal(loid)s in indigenous crab species and human health risk implications - Prince Onyedinma Ukaogo; Jian Tang; Ahamefula Anselm Ahuchaogu; Okenwa Uchenna Igwe; Anthony I. Obike; Precious Onyinyechi Emole; Loai Aljerf; Ojah Emmanuel Onah; Ali Tijjani; Atem Bethel Ajong (Emerging Contaminants, 2022)
Despite the nutritional benefits of crab consumption, the bioaccumulation of hazardous trace metals (loid) in crabs can endanger consumers’ health. The consumption of crab has received less attention. As, Cd, Cr, Cu, Li, Hg, Fe, Pb and Zn in four common crab species collected from the bank of selected streams and the associated health risks were analyzed for the consumers by evaluating estimated weekly intake (EWI), non-carcinogenic and carcinogenic health risks to children, adolescents, and adults. In this study, 320 samples were collected in total. These crab and sediment samples showed a descending average content of Fe > Zn > Cu > Cr > Pb > As > Cd > Li > Hg, respectively. EWI values of children, adolescents, and adults were all lower than provisional tolerable weekly intakes (PTWIs) of all crab species. According to the toxic hazard quotient (THQ) and the total hazard index (HI) calculations for trace metal contents in the crabs, mercury did not pose any risk to human health; whereas, the other determined trace metals (loid) gave the values of HI > 1 and showed a possibility of risk on the long term. In all age groups, the consumption of U. tangeri, O. Africana, and C. armatum would lead to lifetime cancer risk due to As and Cd bioaccumulation. Also, Statistical analysis reveals the origin of the contaminants in the crabs, and indicate that Cr, Zn, Pb, and Cd are from anthropogenic activities while the other metals originate from natural lithogenic actions.